(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Myxopyrum smilacifolium is a large woody climbing shrub belonging to the family Oleaceae which is known for many medicinal properties. In the present study, initially a short term cytotoxic study (3 hours) with hepatocarcinoma cell line HepG2 using Trypan Blue Assay was carried out against methanolic extracts of root and callus and found an appreciable result for both extracts. Then the study was extended to the same cell line employing MTT assay. In this procedure extracts were subjected to 24 hours treatment and cytotoxicity was measured using a colorimetric method based on the ability of metabolic active cells to cleave the yellow tetrazolium salt MTT to an insoluble purple formazan crystal. A concentration dependent activity was observed in both Trypan Blue as well as MTT assay. The results showed that both the extracts possess potent cytotoxic activity. IC50 value from MTT assay was found to be 63.75µg/l and 98.75µg/l for root and callus extracts respectively. To the best of our knowledge, this is the first study to demonstrate the cytotoxic potential of callus extracts of Myxopyrum smilacifolium Blume.